Analisis Kebutuhan Pengembangan Instrumen Penilaian Kemampuan Berpikir Geometri Berbasis Website - Fardiana, Rina; Supriyadi; Djuniadi (Department of Mathematics Education, Faculty of Tarbiyah and Teacher Training, UIN Sunan Ampel Surabaya, 2023)
The ability to think geometrically is hierarchical so students need to master the initial level of thinking before they are going to the next level. Geometry learning strategies need to consider the level of students' thinking abilities. Assessment with paper-based tests has weaknesses in terms of practicality and does not develop students' technological literacy in the digitalization era. This study aims to analyze the need for the development of a website-based instrument to assess the geometric thinking skills of elementary school students referring to Van Hiele's theory. This research is a literature review with a qualitative approach. The articles reviewed in this research are articles that discuss thinking skills based on Van Hiele's theory with research subjects of elementary school students and published from 2021 to 2023. Data were analyzed by Miles and Huberman's interactive model. The results showed that a web-based instrument for assessing the geometric thinking abilities of elementary school students based on Van Hiele's theory was needed to systematically assess students' geometric thinking abilities then could be followed up with learning activities according to students' abilities. The level of thinking of elementary school students assessed is from visualization to abstraction which is adapted to the material and curriculum of the elementary school.